The use of BCAP in Finland: toward correct classification rate - Paavilainen Eija; Ellonen Noora; Mielityinen Laura (Taylor & Francis Group, 2022)
AbstractObjective Further validation of Brief Child Abuse Potential (BCAP) inventory, for setting the correct classification rate.Methods Data collection from potential abusers (n = 47), visiting in the hospital clinic meant for parents having special needs due to problems with alcohol and drugs connected to other evidence-based risk factors of child abuse. The risk level was compared between these 47 parents and previously collected data from 450 parents, representing general population.Results There were no differences between likely abusers and the general population. Among both groups, 6% had elevated abuse risk and there were no differences in appearance of dimensions including in the abuse scale.Conclusions Assuming child abuse based on known risk factors is not enough, when setting the correct classification rate. We need more accurate knowledge about the abuse, and the family life situation in general. However, assessing risk factors of child maltreatment systematically with the BCAP, can still serve as a fruitful basis of assessing parents' needs and worries as the basis for providing support what they need.